Notifiable disease surveillance in Sri Lanka and the United Kingdom: a comparative study - Chandrasekar, K.; Mahesan, S.; Bath, P.A. (Sri Lanka Journal of Bio-Medical Informatics, 2013)
Threats posed by new, emerging or re-emerging infectious diseases are taking a global dimension. These diseases are a leading cause of morbidity and mortality around the world and have an influence on the economic growth and development of nations. Several evaluation studies on existing infectious disease surveillance systems (passive and/or active) have been undertaken to identify the strengths and weaknesses in order to improve surveillance activities. Research is also directed towards identifying specific factors that influence the information flow in the notification process of infectious diseases at different levels, such as completeness, timeliness, sensitivity, etc. Studies reported from Sri Lanka and the United Kingdom are very limited. Further, we rarely find any literature on comparative studies on disease surveillance systems in two different geographical locations. In this study in-depth, semi-structured interviews were conducted to collect data, in Jaffna (Sri Lanka) and Sheffield (UK). Participants were recruited from those who were engaged in work related to the notifiable disease surveillance system at a local level. This research paper reports the advantages and disadvantages of the existing notifiable disease surveillance systems in the United Kingdom and Sri Lanka. In addition, it recommends that receiving notifications from various other sources (including indigenous medical practitioners, public health workers, laboratories and the general public), involvement of laboratories in disease surveillance activities, and computerising the existing surveillance system for notification would enhance the completeness and timeliness of reporting. In addition to epidemiological publications at national level, this study emphasises the importance of regional publications on notifiable disease surveillance.
Keywords: communicable disease surveillance; disease notification; infectious diseases